The Role of Musical-rhythmic Movements of Children of Pre-school Age in the Process of Vocal-choral Activity - Maiba, Olha (Journal of History Culture and Art Research, 2019)
The article focuses on the role of musical-rhythmic movements of children of pre-school age in the vocal-choral activity process. It was found out that musical-rhythmic movements in vocal-choral art are aimed at attracting children to universal cultural values, contributing to the development of artistic taste and emotional manifestations of the child, the education of positive forms of behavior and communication. Musical-rhythmic movements are one of the means of musical education and training in pre-school educational institutions. The basic tasks and pedagogical principles for the learning of musical-rhythmic movements of preschool children in the process of vocal-choral activity, which contribute to the synthesis of results, are determined. Thus, the development of the activities of preschoolers, the perception of the musical form of vocal and choral work, the comparison of contrasting and similar musical constructs, tune coloring, features of the rhythmic pattern, dynamics, tempo - everything can be reflected in musical-rhythmic movements.